Long-term exposure to fine particle matter and all-cause mortality and cause-specific mortality in Japan: the JPHC Study - Norie Sawada; Tomoki Nakaya; Saori Kashima; Takashi Yorifuji; Tomoya Hanibuchi; Hadrien Charvat; Taiki Yamaji; Motoki Iwasaki; Manami Inoue; Hiroyasu Iso; Shoichiro Tsugane (BMC, 2022)
Abstract Background Many epidemiological studies have reported the association between exposure to particulate matter and mortality, but long-term prospective studies from Asian populations are sparse. Furthermore, associations at low levels of air pollution are not well clarified. Here, we evaluated associations between long-term exposure to particulate matter <2.5 µg/m3 (PM2.5) and mortality in a Japanese cohort with a relatively low exposure level. Methods The Japan Public Health Center-based Prospective Study (JPHC Study) is a prospective cohort study of men and women aged 40-69 years in 1990 who were followed up through 2013 for mortality. In this cohort of 87,385 subjects who did not move residence during follow-up, average PM2.5 levels from 1998 to 2013 by linkage with 1-km2 grids of PM2.5 concentration were assigned to the residential addresses of all participants. To avoid exposure misclassification, we additionally evaluated the association between 5-year (1998-2002) cumulative exposure level and mortality during the follow-up period from 2003 to 2013 in 79,078 subjects. Cox proportional hazards models were used to calculate the association of long-term exposure to PM2.5 on mortality, with adjustment for several individual confounding factors. Results Average PM2.5 was 11.6 µg/m3. Average PM2.5 exposure was not associated with all-cause mortality or cancer and respiratory disease mortality. However, average PM2.5 was positively associated with mortality from cardiovascular disease (hazard ratio (HR) of 1.23 (95%CI=1.08-1.40) per 1-µg/m3 increase; in particular, HR in mortality from cerebrovascular disease was 1.34 (95%CI=1.11-1.61) per 1-µg/m3 increase. Additionally, these results using cumulative 5-year PM2.5 data were similar to those using average PM2.5 over 15 years. Conclusions We found evidence for a positive association between PM2.5 exposure and mortality from cardiovascular disease in a Japanese population, even in an area with relatively low-level air pollution.